2019
DOI: 10.29252/ijree.4.4.40
|View full text |Cite
|
Sign up to set email alerts
|

From Collective Activity to Autonomous Learning: Fostering Learner Autonomy in Light of Activity Theory

Abstract: Autonomous learning and social activity have excessively been the focus of interest in second language acquisition over the past decades. The present study aimed to explore how activity theory-as a branch of sociocultural theory focusing on social context-can promote Iranian EFL learners' autonomy. To this end, fifty-six EFL students studying English translation at Islamic Azad University, Tehran Central Branch, participated in the study. The participants were assigned to two groups, one experimental group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…As evidenced by the relevant literature in the field, the enhancement of learner autonomy has a significant positive impact on student learning. It has received considerable research interest since 1981 as there have been many research studies focusing on teachers' and students' perceptions, beliefs or attitudes towards learner autonomy (Alhaysony, 2016;Alonazi, 2017;Asiri & Shukri, 2020;Asmari, 2013;Bekleyen & Selimoglu, 2016;Cirocki, Anam, & Retnaningdyah, 2019;Dogan & Mirici, 2017;Duong, 2014;Hajimaghsoodi & Saghaieh Bolghari, 2019;Khalil & Ali, 2018;Shahsavari, 2014;Tuan, 2021). Most of these studies have concluded that while both teachers and students have a positive attitude toward learner autonomy, they are not autonomous practically.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…As evidenced by the relevant literature in the field, the enhancement of learner autonomy has a significant positive impact on student learning. It has received considerable research interest since 1981 as there have been many research studies focusing on teachers' and students' perceptions, beliefs or attitudes towards learner autonomy (Alhaysony, 2016;Alonazi, 2017;Asiri & Shukri, 2020;Asmari, 2013;Bekleyen & Selimoglu, 2016;Cirocki, Anam, & Retnaningdyah, 2019;Dogan & Mirici, 2017;Duong, 2014;Hajimaghsoodi & Saghaieh Bolghari, 2019;Khalil & Ali, 2018;Shahsavari, 2014;Tuan, 2021). Most of these studies have concluded that while both teachers and students have a positive attitude toward learner autonomy, they are not autonomous practically.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%